Soft tissue sarcomas - Purriel, Juan A; Guzmán, P (Cirugía del Uruguay, 1973)
Sarcomas of soft parts are defined as malignant tumors arising in the tissues between dermis and periosteum and covering the. skeleton of the trunk and limbs. Generally these neoplasias are mesodermic in origin with the exception of tumors in peripheral nerve sheaths which are of neuroectodermic origin. The multipotential character of mesenchymatose cell determine that these tumors present marked structural complexity, thus making histogenetic diagnosis difficult. On the other hand, no other tumoral origin shows so evidently -the relative character of histological malignancy, and consequently we have found convenient to est.ablish three. degrees (local, regional and general) of malignancy according to morphologic and evolutive characteristics of each tumoral type. We propase a histogenetic classification which comprises ali tumoral forros with their histopathological and biological characteristics; we insist, above ali, in fibroblastic tumors, where discordancy is often found between morphologic and evolutive characteristics. Finally we study a series of 20 cases of sarcomas of soft parts, their frequency and evolution pre and post-treatment. Even though this sample has little significance, incomparing it with Stout's broader series, ( 1953) their was marked similarity in their general characteristics.